The Nature of Trade and Growth Linkages - Didier, Tatiana; Pinat, Magali (World Bank, Washington, DC, 2017)
This paper shows new empirical regularities indicating that the structure of trade connections affects the trade-growth nexus. System generalized method of moments estimations indicate that key structural features associated with the composition of traded products and partners matter for growth. The results show that increases in the degree of intra-industry trade, greater insertion into the middle of global value chains, and increases in the shares of differentiated goods, skilled labor-intensive goods, and high-tech-intensive goods in traded baskets are all associated with higher income growth. An increase in the share of trade with countries at the core of the global trade network is also associated with greater growth effects. However, many of these effects are non-linear and depend on the degree of trade openness and labor force education. The results suggest that technological diffusion and learning spillovers play some role in the growth effects associated with the nature of trade connections.